Casa do Sertão: Museum, Identity and Territory - Lima Carvalho e Lima, Claudia Roberta (2025)
Museums are institutions capable of constructing signs and meanings of identity in a territory. The objective of this research was to analyze how the territory and country identity are integrated into the Casa do Sertão Museum, an institution linked to the State University of Feira de Santana. We also sought to analyze the role of museums and museology in the construction of national and regional identity, in light of postmodern discussions about identity. This descriptive study has an applied purpose in the field of Museology, with transversal themes of Geography. It was carried out in a qualitative approach, with bibliographic and documentary reviews. As a result, it was evident that the institutional structure of Casa do Sertão causes it to present territory and identity without considering the power relations that permeate its definitions. It was concluded that the museum needs financial and management autonomy to act in a more innovative way, which will allow the expansion of the discussion on the symbolic construction of the territorial identity that underpins its existence.